2015
DOI: 10.48550/arxiv.1504.08201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of the electric field on the creation of fermions in de-Sitter space-time

S. Haouat,
R. Chekireb

Abstract: The effect of the electric field on the creation of spin 1/2 particles from vacuum in the (1+1) dimensional de-Sitter space-time is studied. The Dirac equation with a constant electric field is solved by introducing an unitary transformation. Then the canonical method based on Bogoliubov transformation is applied to calculate the pair creation probability and the density of created particles both for positive or negative wave vector. By doing summation over all allowed states, the number of created particles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…This effect is used as an explanation for the generation of primordial cosmic inhomogeneities which in turn can explain the large scale structure of the universe. Recently also the combination of the effects of the gravitational and electric field have been studied in various frameworks [21][22][23][24][25][26][27][28]. As the flat Minkowski spacetime, D-dimensional de Sitter (dS D ) spacetime has constant scalar curvature and is maximally symmetric.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is used as an explanation for the generation of primordial cosmic inhomogeneities which in turn can explain the large scale structure of the universe. Recently also the combination of the effects of the gravitational and electric field have been studied in various frameworks [21][22][23][24][25][26][27][28]. As the flat Minkowski spacetime, D-dimensional de Sitter (dS D ) spacetime has constant scalar curvature and is maximally symmetric.…”
Section: Introductionmentioning
confidence: 99%
“…The regularized current of scalar QED has recently been computed in dS 2 using Pauli-Villars subtraction in [25] and in dS 4 using adiabatic regularization in [26]. While fermionic pair creation in dS 2 has been studied [23,24,27] the computation of the current has not been performed. Here we will compute the fermionic current in dS 2 and regularize it using adiabatic regularization.…”
Section: Introductionmentioning
confidence: 99%
“…The density of state has been proposed for spinor QED in the dS space. 32 5. QED Action Density in (A)dS 2…”
Section: Density Of Statesmentioning
confidence: 99%
“…Due to the cosmological event horizon dS emits particles [10,11,19,[36][37][38][39][40][41][42][43][44] which is known as the Gibbons-Hawking radiation [45,46]. In a dS, by using semiclassical approaches the Schwinger effect for scalar [47][48][49][50][51][52][53][54][55][56][57][58] and Dirac [59][60][61][62][63][64][65] fields has been investigated which may amplifies the Gibbons-Hawking radiation. Perturbative amplitude for production of the scalar [66][67][68][69][70] and Dirac [71][72][73] pairs in the presence of an electric field on the dS has been studied and the authors found that the pair production is significant only when the expansion parameter is large compered to the mass of the field.…”
Section: Introductionmentioning
confidence: 99%